Neogenin-loss in neural crest cells results in persistent hyperplastic primary vitreous formation. (23rd July 2019) - Lin, Sen; Liu, Wei; Chen, Chun-Lin; Sun, Dong; Hu, Jin-Xia; Li, Lei; Ye, Jian; Mei, Lin; Xiong, Wen-Cheng
Abstract: Neogenin is a transmembrane receptor critical for multiple cellular processes, including neurogenesis, astrogliogenesis, endochondral bone formation, and iron homeostasis. Here we present evidence that loss of neogenin contributes to pathogenesis of persistent hyperplastic primary vitreous (PHPV) formation, a genetic disorder accounting for 5% of blindness in the USA. Selective loss of neogenin in neural crest cells (as observed in Wnt1 -Cre; Neo f/f mice), but not neural stem cells (as observed in GFAP -Cre and Nestin -Cre; Neo f/f mice), resulted in a dysregulation of neural crest cell migration or delamination, exhibiting features of PHPV-like pathology (e.g. elevated retrolental mass), unclosed retinal fissure, and microphthalmia. These results demonstrate an unrecognized function of neogenin in preventing PHPV pathogenesis, implicating neogenin regulation of neural crest cell delamination/migration and retinal fissure formation as potential underlying mechanisms of PHPV.